STM32-Based Intelligent Badminton Pickup and Launch Robot - Jiang, Zehui; Xu, Shuqiong; Yang, Shu; Yang, Qing (IEEE Advanced Information Technology, Electronic and Automation Control Conference (IAEAC) (Online), 2024)
This paper outlines the application value and future development direction of intelligent badminton pickup and launch robots in the sports industry. This project promotes the development of the sports industry by realizing the integration of badminton robot picking up and launching badminton balls. Utilizing the openmv vision module to control the high torque planetary gear motor and McNamee wheel, it can carry out all-around intelligent automatic identification of badminton balls and plan the path for picking up. Using STM32F4xx series microcontroller for serial communication to connect the motor drive module to control the speed of the high speed brush motor, it can control the height, distance, left and right position of the badminton ball launching, so as to satisfy the user's demand for the development of badminton technology in all aspects. In summary, by combining the STM32F4xx series microcontroller algorithm, openmv vision algorithm and motor drive module and other embedded control technology, for the sports industry to bring intelligent automation experience and development.